POTENSI RUMAH KOS-KOSTAN DI SAMARINDA UNTUK MENJADI MATA PENCAHARIAN RAKYAT YANG MENGHASILKAN INCOME SEHINGGA MENJADI PROFESI - Florentinus Sudiran (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
The obyective of  this research is to know how to found the boarding house as well as the rented house .The location of it is in Samarinda City , Kalimantan in November 2017 for thirty days.The result ofe the research are (1).At the beginning to choose the location of the rented house, (2)To count the number of expected persons who will be tenants,(3)To count the rented house presented here before,(4).Survey to know the price f the land , houe,rented house,the buliding cost /square in the surrounding and the future expection(5)To look for the strategic locations ,(6)To know the security in the surroundings,(7)Condition related with natural detruction such as flood, storm and the like,(9)The consumers wether the majorit   of the consumer the man or the woman,(10).The access of the transportation,(11)  The kinds of the room type and facility selected by the consumers,(12) The distance to the the market or the shop of the main need. The suggestions of this research results are (1)To build a rented house has to be strategic,it means the one which are hort distance to go to the shop , school,markets, industry and hospitals (2) The number of the expected tenants has to be got by survey, (3)To survey the rivals of the rented huse concerned,(4)To count the prices of the land , house  contractor and the deveopment of the location,(5) The security has to be condusive  relating with the flood  storm, clean water and the wild animals.